The Role of Literature in Enriching National Culture and Identity - Rosmawaty Harahap; Gita Malem Br Karo Sekali (Winaya Inspirasi Nusantara Foundation, 2025)
Literature plays an important role in enriching a country's culture and national identity. The purpose of this study is to examine the contribution of literature in this context through a detailed literature review. A structured approach is used to explain the importance of understanding how literature expresses culture, values and national identity. The research method includes the study of literature from various sources, including books, magazine articles, literary works, statistical data, and cultural reports. The main findings show that literature not only reflects cultural reality but also reflects deeply the values expressed in society. Literary works reflect the daily life, traditions and struggles of a nation. The results of this study highlight the importance of understanding the role of literature in strengthening cultural identity and nationalism. The implications of these findings can help guide future educational and cultural policies.